Malay Leadership Model from an Institutional Economic Perspective in the Riau Islands - Chairinnisa’Ramadhani; Meisya Tania Putri; Melsa Santiya; Satriadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the Malay leadership model in the Riau Islands, which is rooted in local cultural values, particularly trust, etiquette, deliberation, and moral responsibility in leadership practices. The objectives of this study are to understand the meaning of Malay leadership, identify its distinctive characteristics compared to other leadership models, and analyze its relevance in the context of contemporary leadership challenges. This study employs a qualitative approach by collecting primary data through interviews and observations, supported by documentary studies as secondary data sources.The findings reveal that Malay leadership emphasizes harmony between spiritual, moral, and social values. The core characteristics of this leadership model include integrity, honesty, wisdom, politeness, and the balance between inner and outer character. In addition, the principles of deliberation (musyawarah), consensus-building, and maintaining social harmony serve as the foundation for decision-making processes within society and organizations. The study also finds that the preservation of Malay leadership values is conducted through succession processes managed by customary institutions, which play an important role in shaping future leaders with strong moral character and cultural awareness. The novelty of this study lies in its focus on the Malay leadership model in the Riau Islands as a local culture-based leadership framework, which has received limited attention in previous leadership studies. Unlike prior research that predominantly discusses universal leadership theories such as transformational or transactional leadership, this study specifically explores the integration of Malay cultural values into leadership practices and examines their relevance in contemporary organizational and social contexts. Therefore, this study contributes to strengthening leadership studies based on local wisdom and offers an adaptive, culturally grounded, and sustainable alternative leadership model.